Numerical Study Of Fatigue Crack Growth At A Web Stiffener Of Ship Structural Details - Wentao He; Jingxi Liu; Xie, De (Zenodo, 2014)
It is necessary to manage the fatigue crack growth (FCG) once those cracks are detected during in-service inspections. In this paper, a simulation program (FCG-System) is developed utilizing the commercial software ABAQUS with its object-oriented programming interface to simulate the fatigue crack path and to compute the corresponding fatigue life. In order to apply FCG-System in large-scale marine structures, the substructure modeling technique is integrated in the system under the consideration of structural details and load shedding during crack growth. Based on the nodal forces and nodal displacements obtained from finite element analysis, a formula for shell elements to compute stress intensity factors is proposed in the view of virtual crack closure technique. The cracks initiating from the intersection of flange and the end of the web-stiffener are investigated for fatigue crack paths and growth lives under water pressure loading and axial force loading, separately. It is found that the FCG-System developed by authors could be an efficient tool to perform fatigue crack growth analysis on marine structures. : {"references": ["Fricke W, Paetzold H. Full-scale fatigue tests of ship structures to validate the S\u2013N approaches for fatigue strength assessment. Marine Structures 2010;23: 115\u2013130.", "Serror M, Marchal N. Simulation of behavior of fatigue cracks: a complete industrial process on a typical connection in a FPSO. Proceedings of the ASME 2009 28th International Conference on Ocean, Offshore and Arctic Engineering OMAE2009 May 31 - June 5, 2009, Honolulu, Hawaii.", "Jang BS, Ito H, Kim KS, Suh YS, Jeon HT, Ha YS. A study of fatigue crack propagation at a web stiffener on a longitudinal stiffener. J Mar Sci Technol 2010;15: 176-89.", "Okawa T, Sumi Y, Mohri M. Simulation - based fatigue crack management of ship structural details applied to longitudinal and transverse connections. Marine Structures 2006;19:217 \u2013 40.", "Wentao He, Jingxi Liu, De Xie. Numerical study on fatigue crack growth at a web-stiffener of ship structural details by an objected-oriented approach in conjunction with ABAQUS. Marine Structures 2014, 35:45\u201369.", "Cojocaru D, Karlsson A.M. An object-oriented approach for modeling and simulation of crack growth in cyclically loaded structures. Adv Eng Softw 2008; 39: 995\u20131009.", "ABAQUS 6.11 Scripting User's Manual. HKS Inc.", "ABAQUS 6.11 Scripting Reference Manual. HKS Inc.", "Rybicki EF, Kanninen MF. A finite element calculation of stress intensity factors by a modified crack closure integral. Engng Fract Mech 1977; 9:931-938.\n[10]\tXie D, Biggers Jr. SB. Progressive crack growth analysis using interface element based on the virtual crack closure technique. Finite Elem Anal Des 2006; 42: 977-84.\n[11]\tXie D, Biggers Jr SB. Strain energy release rate calculation for a moving delamination front of arbitrary shape based on virtual crack closure technique, Part I: formulation and validation. Engng Fract Mech 2006; 73: 771\u201385.\n[12]\tXie D, Waas AM, Shahwan KW, Schroeder JA, Boeman RG. Computation of strain energy release rate for kinking cracks based on virtual crack closure technique. CMES\u2014Comp Model Engng Sci 2004; 6: 515\u201324."]}